Comparison of technology and technical efficiency in cereal production among EU countries - Lukas Cechura; Heinrich Hockmann; Michal Malý; Zdenka Žáková Kroupová (Agris on-line Papers in Economics & Informatics, 2015)
The paper presents the analysis of cereal production in the EU. The analysis provides the comparison of production technologies and technical efficiency among EU countries using the country specific multiple output distance function models in the first step and metafrontier approach in the second step to determine the level and development of technical efficiency. The results show the high technical efficiency of cereal producers in the analyzed countries. On average, the differences in technical efficiency among the analyzed countries are not pronounced; however, the technologies used as well as the determinants of technical efficiency differ significantly. – – Článek prezentuje výsledky analýzy produkce obilovin v rámci jednotného trhu EU. Analýza je založena na odhadu multiple output distance (vzdálenostní) funkce pro jednotlivé členské země v prvním kroku a následném odhadu metafrontier multiple output distance funkce v druhém kroku. Komparativní analýza ukazuje na vysokou technickou efektivnost producentů obilovin v analyzovaných zemích. Z výsledků plyne, že mezi zeměmi EU neexistují výrazné rozdíly v technické efektivnosti, přestože značnou rozdílnost vykazují v produkčních technologiích i v determinantech technické efektivnosti.
Keywords: 330; cereal production; multiple output distance function; technical efficiency; technology; metafrontier analysis; SFA; obiloviny; vzdálenostní funkce; technická efektivnost; technologie; metafrontier analýza